1987
DOI: 10.1007/bf03015340
|View full text |Cite
|
Sign up to set email alerts
|

Fibreoptic bronchoscopy for tracheal and endobronchial intubation with a double-lumen tube

Abstract: A 68-year-old patient was scheduled for a thoracotomy. A double-lumen endobronchial tube was requested by the surgeon to facilitate operating conditions. Initial attempts at intubation by conventional methods were unsuccessful. The proximal ends of a 37F double-lumen tube were then shortened and a 4-mm fibreoptic bronchoscope was passed through the bronchial lumen. The patient's larynx was easily visualized and the bronchoscope was passed into the trachea. The double lumen tube was then advanced over the bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Some studies showed that direct intubation with the DLT over a fiberoptic bronchoscope would be more difficult than the same for SLT 9 13 . Only two case reports showed that direct intubation with a polyvinyl chloride DLT over the fiberoptic bronchoscope was actually implemented in the awake state or using a shortened DLT 5 , 6 . Our previous study results demonstrated that direct tracheal intubation with the silicone DLT using the fiberoptic bronchoscope was fast and had a similar performance as that of polyvinyl chloride SLT 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that direct intubation with the DLT over a fiberoptic bronchoscope would be more difficult than the same for SLT 9 13 . Only two case reports showed that direct intubation with a polyvinyl chloride DLT over the fiberoptic bronchoscope was actually implemented in the awake state or using a shortened DLT 5 , 6 . Our previous study results demonstrated that direct tracheal intubation with the silicone DLT using the fiberoptic bronchoscope was fast and had a similar performance as that of polyvinyl chloride SLT 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, it would be easier and safer to initially place an SLT using video laryngoscopy or a flexible fiberoptic bronchoscopy and then replace it with a DLT using an airway catheter exchanger technique 1 , 2 , 4 . However, the characteristics of DLT mentioned earlier could also cause railroading (advancement over the fiberoptic bronchoscope or tube exchanger) to be traumatic and difficult 5 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Haitov et al showed that DLT insertion was simple and safe in 5 cases with difficult airways [9]. Shulman et al also reported direct fiberoptic intubation using a shortened DLT in a case where intubation using a variety of laryngoscope blades failed [10]. However, due to the intuitive characteristics derived from polyvinyl chloride DLTs, such as a large shaft, long length, and low flexibility, the assumption that direct insertion of a DLT via an FOB is difficult and traumatic has long been accepted [11][12][13][14][15][16][17], but no comparative studies have proved this concept.…”
Section: Introductionmentioning
confidence: 99%